Trident-shaped multimodal piezoelectric energy harvester - Upadrashta, Deepesh (2020)
Energy harvesting from ambient vibrations using piezoelectric materials has garnered much research focus over the years due to its immense potential to replace/recharge batteries in wireless sensor nodes and low-power-consuming autonomous electronic devices. Practical implementation of conventional linear piezoelectric energy harvesters is not an effective solution because they suffer from narrow operational bandwidth due to their single resonant peak response in frequency spectrum. Several techniques, such as oscillator arrays, passive/active resonant tuning, and nonlinear methods, have been proposed to broaden the bandwidth of harvesters. This paper proposes a novel trident (three-pronged spear) shaped multimodal (three degrees of freedom) piezoelectric energy harvester to harness electrical energy from wideband, low-frequency, and low-amplitude ambient vibrations. A single patch of piezoelectric material is used for power generation from multiple modes of the structure. The harvester structure consists of a primary cantilever beam with a patch of macrofiber composite bonded on it and three branched beams with tip masses attached to the free end of the primary beam. The first three bending modes of the harvester are used for power generation. The proposed harvester can be designed to operate in the frequency range of the target vibration source. A parametric study varying the geometric parameters of the harvester is conducted using ANSYS finite-element analysis software to obtain the three resonant peaks in the 15-20 Hz bandwidth. The prototype of multimodal harvester is fabricated in accordance with the parametric study and tested under harmonic and random excitations. When tested at 0.2grms harmonic excitation, the harvester generates 3738, 47, and 123 μW at the three resonant peaks. When tested under random excitation, the harvester accumulates sufficient energy in a capacitor to support a low-power standalone wireless sensing unit.